Uranium and Religion: Toward a Decolonial Temporality of Extraction - Amanda M. Nichols (Religions)
Uranium mining for the production of nuclear technologies has left visible scars across the United States and perpetuated legacies of extraction that extend beyond material consumption to the exploitation of people and the environment. Influenced by important ongoing conversations in the environmental and energy humanities, posthumanism, and decolonial studies, I analyze how uranium extraction has been conceived of as an “event” within a colonial temporal framework. A critical examination of how religious worldviews have informed the ways that time is conceptualized and understood shifts thinking about extraction away from colonial temporalities and helps reimagine extraction through a decolonial perspective as temporally distributed, enmeshed, and complex. This reframing is imperative to foster an understanding that the radioactive byproducts of uranium created through the nuclear production process are globally dispersed, will persist across generations, and will have transgenerational implications for human and non-human organisms and the health and viability of ecologic systems.